Hubungan Antara Kopi Dengan Kondisi Ginjal - Aina Salsabila Muslim (Jurnal Medika Hutama, 2021)
Coffee is a plantation plant that belongs to the genus Coffea with the family Rubaceae. Coffee is used as a drink by the world community. Some of the compounds contained in coffee are one of the bioactives in coffee that have an influence on kidney conditions. The purpose of this paper is to determine the relationship between coffee and kidney conditions. The method used is a literature review by searching for the keywords coffee, kidney, glomerulus, and tubule on Google Scholar and Pubmed. Searching the literature from both national and international journals then summarizes the discussion topics and compares the results presented in the articles. From several studies conducted, the relationship between coffee and kidney condition is to reduce the number of renal glomerular mesangial cells, prevent glomerular hypertrophy, and cause thyroidization of renal tubular epithelial cells.